The Status Of Grondkaart As A Tool Of Proof Of Land Registration In Indonesia - W. Wardhani, Dinar; Gusti Ayu Ketut Rachmi Handayani, I; Karjoko, Lego (International Journal of Educational Research & Social Sciences, 2023)
Grondkaart as one of the basis of control over land owned by individuals or legal entities, one of which is PT. KAI (Persero). The unclear position of grondkaart in the systematics of laws and regulations has resulted in various land tenure disputes. The purpose of this research is to provide information and legal consequences of grondkaart as evidence of land registration in Indonesia. The method used is a normative juridical approach with literature review on laws and civil cases in court. Grondkaart as evidence of land tenure and guidance because it refers to article 97 PP Number 18 of 2021, Besluit No 3 of 1890, there is no provision for the conversion of the UUPA, and it is not mentioned in one of the proofs of new rights based on PP Number 24 of 1997.